Hortinlea baseline survey report 2014 - Sindu Workneh Kebede; Henning Krause; Evans Ngenoh; Hillary Kiplangat Bett; Anja Faße; Wolfgang Bokelmann (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This report summarizes major findings from the HORTINLEA survey conducted in 2014 under the framework of HORTINLEA project. The HORTINLEA project is an inter-disciplinary research project addressing food security in East Africa, particularly in Kenya. The project targets to improve the livelihood and nutritional situation of the rural and urban poor. To achieve this, it focuses on production and consumption of horticultural crops, especially of African indigenous vegetables (AIVs). The HORTINLEA survey, conducted in rural, peri-urban and urban areas of Kenya focused on AIV actors along the value chain namely: producers, traders and consumers. The survey was carried out in September and October, 2014 where data was collected at the household, plot and community levels. It was administered using structured questionnaire with Geo-codes where more than 1500 actors were interviewed along the AIV value chain. Various topics were covered in the survey including household composition, education, health, assets, expenditure, credit and saving, agricultural and AIV production, agricultural and AIV marketing, nutrition, shocks and coping strategies. The most widely produced African Indigenous vegetable is African nightshade produced by about 72 procent of respondents followed by cowpeas produced by about 48 procent of respondents. [...] – – Dieser Bericht fasst die wichtigsten Ergebnisse der HORTINLEA-Umfrage zusammen, die 2014 im Rahmen des Projekts HORTINLEA durchgeführt wurde. Das HORTINLEA-Projekt ist ein interdisziplinäres Forschungsprojekt zur Ernährungssicherheit in Ostafrika, insbesondere in Kenia. Das Projekt zielt darauf ab, die Lebensgrundlage und die Ernährungssituation der armen ländlichen und städtischen Bevölkerung zu verbessern. Um dies zu erreichen, konzentriert sie sich auf die Produktion und den Konsum von Gartenbaukulturen, insbesondere von einheimischem afrikanischem Gemüse (AIVs). Die HORTINLEA-Umfrage, die in ländlichen, peri-urbanen und städtischen Gebieten Kenias durchgeführt wurde, konzentrierte sich auf AIV-Akteure entlang der Wertschöpfungskette: Produzenten, Händler und Verbraucher. Die Umfrage wurde im September und Oktober 2014 durchgeführt, wobei Daten auf Haushalts-, Grundstücks- und Gemeindeebene erhoben wurden. Es wurde mit Hilfe eines strukturierten Fragebogens mit Geo-Codes durchgeführt, bei dem mehr als 1500 Akteure entlang der AIV-Wertschöpfungskette befragt wurden. Verschiedene Themen wurden in der Umfrage behandelt, darunter Haushaltszusammensetzung, Bildung, Gesundheit, Vermögen, Ausgaben, Kredite und Ersparnisse, landwirtschaftliche und AIV-Produktion, landwirtschaftliches und AIV-Marketing, Ernährung, Schocks und Bewältigungsstrategien. [...]
Keywords: Q12; Q13; R20; 330; African indigenous vegetables (AIV); household characteristics; household welfare; AIV production; AIV marketing; Kenya